Zooplankton of water bodies on the territory of Dvorichanskyi National Park - Колесник, А. М. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2014)
The results of the study of zooplankton communities of various water bodies e.g. river, lakes, temporal water bodies within the boundaries of Dvorichanskyi National Park are presented. During investigation period 36 species of hydrobionts are detected. In whole species composition of zooplankton is typical for the reservoirs of North-Eastern Ukraine.